Exploratory study of quality and excellence approaches and continuous improvement from the perspective of new institutionalism - Karmen Kern Pipan; Boéstjan Gomiéscek; Janez Mayer (Journal for East European Management Studies, 2012)
This paper is based on the findings of empirical research conducted in 110 Slovenian companies. Using statistical methods, we examine the effect of the EFQM Excellence Model on the institutionalization of total quality management (TQM) tools and approaches, as well as financial results to motivate TQM implementation. Within the whole group of companies, special attention was paid to the results of applicants for the Slovenian Business Excellence Prize (SBEP), which were compared with other companies. The SBEP group showed better results compared with the other companies with regards to benchmarking, peer assessment, participation in quality and excellence awards, knowledge sharing, self-assessments and financial results. – – Dieser Artikel basiert auf den Ergebnissen einer empirischen Untersuchung in 110 Slowenischen Unternehmen. Durch die Anwendung statistischer Methoden untersuchten wir die Wirkung des EFQM Excellence Modells auf die Institutionalisierung der Total Quality Management (TQM) - Werkzeuge und Ansätze sowie finanzielle Ergebnisse, um eine Umsetzung des TQM zu motivieren. Innerhalb der gesamten Gruppe von Unternehmen wurde besonderes Augenmerk auf die Ergebnisse der Bewerber für den Slowenischen Business Exzellenz Preis (SBEP) gerichtet. Die SBEP Gruppe zeigte bessere Resultate bezüglich Benchmarking, Peer-Beurteilung, Teilnahme am Wettbewerb für die Qualität und Exzellenz Preise, Stimulation des Wissenstransfers, Selbstbewertung und finanziellen Ergebnissen.
Keywords: 650; total quality management; quality and excellence award; EFQM Excellence Model; institutional theory; continuous improvement